2018
DOI: 10.4236/ajcc.2018.72012
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Expression of <i>Sub</i>1 Gene and Association with Submergence Stress Related Traits in Advance Rice (<i>Oryza sativa</i> L.) Genotypes as a Tool of Climate Change Adaptation

Abstract: Floods have now become most detrimental natural catastrophe worldwide due to radical climatic fluxes. Therefore, there is a dire necessity to develop a high yielding rice lines to deal with this scenario. For this purpose, a large scale experiment was conducted including one hundred and fifteen (115) rice genotypes having SUB1 gene imported from International Rice Research Institute (IRRI) Philippines, six local cultivars/approved varieties and three high yielding rice varieties i.e. Sabitri, IR6 and NSICRC222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A decreasing trend in effective tillers hill -1 was shown by all the varieties as the duration of submergence increased. The formation of tiller bud might hamper due to submergence and it might cause a reduction of effective tillers hill -1 (Fukao et al, 2006;Haider et al, 2018). The lack of oxygen for respiration or accumulation of ethylene might inhibit tiller bud formation and growth.…”
Section: Discussionmentioning
confidence: 99%
“…A decreasing trend in effective tillers hill -1 was shown by all the varieties as the duration of submergence increased. The formation of tiller bud might hamper due to submergence and it might cause a reduction of effective tillers hill -1 (Fukao et al, 2006;Haider et al, 2018). The lack of oxygen for respiration or accumulation of ethylene might inhibit tiller bud formation and growth.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of inundation in swamps, especially in the freshwater wetland, will be more severe if there is erratic rainfall due to global climate change. Inundation will occur if rainfall increases both in intensity and frequency [14,15]. The plant will sink if the rainfall conditions are above average (La Nina).…”
Section: Potential Constraints and Characteristics Of Swamplandmentioning
confidence: 99%
“…One study found that this system can increase production by 20% [15,16], while another study found that this system can increase plant population and lowland rice production by 33.07% compared to the conventional system [17,18]. Meanwhile, variety-related climate change mitigation and adaptation measures include the development of early-maturing, drought-tolerant [19], submergence-resistant [20] and salinity-tolerant rice cultivars. This study summarizes research findings on the application of several rice cropping systems with climate change-adaptive improved cultivars.…”
Section: Introductionmentioning
confidence: 99%